Improved Properties of Keratin-based Bioplastic Film Blended with Microcrystalline Cellulose: A Comparative Analysis - Alashwal, Basma Yahya; Saad Bala, M.; Gupta, Arun; Sharma, Swati; Mishra, Puranjan (Elsevier Ltd, 2020)
In the present study, bioplastic films were developed using the different ratio of keratin extracted from chicken feathers and cellulose. Firstly, bioplastic (K-60) was developed from the keratin, extracted from the chicken feathers using an alkaline agent (NaOH), and mixed with PVA/glycerol to synthesize protein-based bioplastic. Further, microcrystalline cellulose (2%) was used as an additive to K-60 bioplastic to develop an improved bioplastic (KC-60). The results of functional group analysis using FT-IR, showed the conformational arrangements of the keratin protein have mostly amides I–III and O[sbnd]H groups in the bioplastic reinforced with microcrystalline cellulose and showed the substantial hydrogen bonding. The scanning electron microscopy analysis suggested the appropriate morphologies without edge, holes and cavities. The X-Ray diffraction analysis suggested the strong crystalline characteristics of synthesized bioplastic. Finally, the thermogravimetric analysis of K-60 and KC-60, showed the greater cross-linking efficiency between cellulose and keratin at higher temperature. Therefore, the results presented the development of keratin-based bioplastics with high structural strength and morphology good crystallinity which can be used in biomedical applications and manufacturing of food containers and others.